2022
DOI: 10.3389/fnut.2022.853115
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation and Antioxidant Activities of a Neutral Polysaccharide From Arecanut (Areca catechu L.)

Abstract: A novel neutral polysaccharide designated as PAP1b was isolated from Areca catechu L. by hot water extraction, ethanol precipitation, and column chromatography. PAP1b was mainly composed of mannose, galactose, xylose, and arabinose in a ratio of 4.1:3.3:0.9:1.7, with an average molecular weight of 37.3 kDa. Structural characterization indicated that the backbone of PAP1b appeared to be composed mainly of → 6-β-Manp-(1 →, → 4)-α-Galp-(1 → and → 3,6)-β-Manp-(1 →) residues with some branches, and terminal of (1 →… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Two absorption bands (2,800–3,500 cm –1 and 500–1,700 cm –1 ) were clearly observed for the three polysaccharides. The appearance of a sharp and strong peak between 3,600 and 3,200 cm –1 is associated with -OH stretching due to the large number of intra-molecular and inter-molecular hydrogen bonds in samples ( 39 , 43 ). Peaks at 2,926 cm –1 are associated with asymmetric and symmetric stretching of CH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Two absorption bands (2,800–3,500 cm –1 and 500–1,700 cm –1 ) were clearly observed for the three polysaccharides. The appearance of a sharp and strong peak between 3,600 and 3,200 cm –1 is associated with -OH stretching due to the large number of intra-molecular and inter-molecular hydrogen bonds in samples ( 39 , 43 ). Peaks at 2,926 cm –1 are associated with asymmetric and symmetric stretching of CH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of highly effective and non-toxic natural compounds is seen as a good alternative for the treatment of liver cancer. In recent years, many studies have shown that natural polysaccharides have significant inhibitory effects on tumors (3)(4)(5)(6). Natural polysaccharides have become the main research focus for anti-tumor drugs since they are less toxic and have no side effects in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A Bruker 600 MHz spectrometer equipped with a 1 H/ 13 C double probe was used for NMR analysis at 25°C ( 18 ). An amount of 50 mg dried RATAPW was dissolved in 1 ml D 2 O and frozen three times to exchange H protons into deuterium completely.…”
Section: Methodsmentioning
confidence: 99%